ANALISIS PEMBERDAYAAN MELALUI PELATIHAN PADA UMKM BATIK PAUH TUJUH SUKU DI KAMANG MAGEK KABUPATEN AGAM - Nelsyah Agesty; Muhammad Riski Arliansyah Nasution; Dinda Ayu Riabatari; Mulyadi; Ade Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of training in MSME empowerment programs has not always been able to optimally address business development needs, particularly in batik MSMEs characterized by creativity and local wisdom. This condition is also experienced by Batik Pauh Tujuah Suku MSME in Kamang Magek, Agam Regency, which still faces limitations in production skills, design innovation, and business development. This study aims to analyze empowerment through training at Batik Pauh Tujuah Suku MSME. The research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and then analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that empowerment through training has had a positive impact on improving production skills, design creativity, and the quality of batik products. The empowerment process has reflected the stages of enabling, strengthening, protection, support, and maintenance; however, the maintenance aspect has not been implemented optimally due to the absence of continuous post-training assistance. In addition, the training materials remain focused primarily on technical production skills and have not fully covered business management and marketing aspects. Therefore, more comprehensive and sustainable training programs are needed to enhance the capacity and independence of MSME actors optimally.